2009
DOI: 10.1158/0008-5472.can-08-4783
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Variant III–Induced Glioma Invasion Is Mediated through Myristoylated Alanine-Rich Protein Kinase C Substrate Overexpression

Abstract: Glioblastoma multiforme (GBM) is the most common and most malignant adult brain tumor. A characteristic of GBM is their highly invasive nature, making complete surgical resection impossible. The most common gain-of-function alteration in GBM is amplification, overexpression, and mutations of the epidermal growth factor receptor (EGFR). The constitutively activated mutant EGFR variant III (EGFRvIII), found in f20% of GBM, confers proliferative and invasive advantage. The signaling cascades downstream of aberran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 32 publications
5
64
0
1
Order By: Relevance
“…The fact that we can see increased expression of invasion-promoting proteins in ϩEGFRvIII cells correlates well with the observation Table S1. that EGFRvIII-expressing tumors display higher invasive and proliferative behavior (60). The SRM analysis showed that wtEGFR protein was present at high levels in the ϩEGFR and ϩPE cell lines, but was at nondetectable levels in all other cell lines, including ϩEGFRvIII.…”
Section: Quantitative Analysis Of Secreted Proteins From Gbm Cells Rementioning
confidence: 95%
“…The fact that we can see increased expression of invasion-promoting proteins in ϩEGFRvIII cells correlates well with the observation Table S1. that EGFRvIII-expressing tumors display higher invasive and proliferative behavior (60). The SRM analysis showed that wtEGFR protein was present at high levels in the ϩEGFR and ϩPE cell lines, but was at nondetectable levels in all other cell lines, including ϩEGFRvIII.…”
Section: Quantitative Analysis Of Secreted Proteins From Gbm Cells Rementioning
confidence: 95%
“…Inhibition of MARCKS activity not only reduces airway mucus hypersecretion both in vitro and in vivo (3,5), but also represses inflammatory leukocyte migration and degranulation (6, 7). There have been limited studies on MARCKS in cancer metastasis, but the results have been conflicting (8)(9)(10)(11)(12)(13). This is because MARCKS expression is ubiquitous in various normal and tumor tissues.…”
Section: To the Editormentioning
confidence: 99%
“…MARCKS is a well‐established regulator of migration in multiple cell types. Dysregulation of MARCKS is closely associated with metastasis in a wide range of cancers and is an indicator of poor prognosis 19, 20. MARCKS increases cell motility through the protein kinase B pathway in fibroblasts21 and glial cells 22.…”
Section: Introductionmentioning
confidence: 99%